An Ethic-of-Care Critique of Induced Genetic Mutation in Animals - Josephine Donovan (Journal of Animal Law, Ethics and One Health)
This article proposes an ethic-of-care critique of the current laboratory practice of gene-editing – that is, inducing genetic mutation in animals. An ethic-of-care approach requires taking into consideration the animal’s standpoint or opinion on the procedure. Since these procedures nearly always involve pain, disorientation, stress, and, in many cases, death, most, if not all, animals would refuse consent. The ethic-of-care approach would therefore endorse replacement of these practices, in accordance with the animals’ inferred wishes.